2007
DOI: 10.1002/ange.200603972
|View full text |Cite
|
Sign up to set email alerts
|

Carbon–Fluorine Bond Activation in Fluoroolefins: Clear Documentation of Cooperative CF Bond Activation by Adjacent Metal Centers

Abstract: Ein großer Unterschied: Aus Fluorolefinen, die zwei Iridiumzentren verbrücken, kann ein Fluoridion abgespalten werden, aus an ein einzelnes Metallzentrum gebundenen dagegen nicht. Die gebildeten verbrückenden Fluorvinylgruppen liefern unter weiterer Fluoridabspaltung Vinylidene, während terminale Fluorvinylgruppen nicht reagieren. Ein Fluorsubstituent konnte selektiv durch Wasserstoff oder eine Methylgruppe ersetzt werden (siehe Schema, Tf:Trifluormethansulfonyl).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…In contrast, 1,1‐difluoroethylene has received much less attention, and to our knowledge, only two examples involving its CF bond activation are known, apart from our own preliminary report 9d. The first example demonstrates that [RhCl(PPh 3 ) 3 ] and other related Rh I complexes react with 1,1‐difluoroethylene under hydrolysis conditions to form the carbonyl complex [RhCl(CO)(PPh 3 ) 2 ], in which the carbonyl carbon originates from the difluoroethylene ligand 9a.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…In contrast, 1,1‐difluoroethylene has received much less attention, and to our knowledge, only two examples involving its CF bond activation are known, apart from our own preliminary report 9d. The first example demonstrates that [RhCl(PPh 3 ) 3 ] and other related Rh I complexes react with 1,1‐difluoroethylene under hydrolysis conditions to form the carbonyl complex [RhCl(CO)(PPh 3 ) 2 ], in which the carbonyl carbon originates from the difluoroethylene ligand 9a.…”
Section: Introductionmentioning
confidence: 81%
“…Our emphasis in activating fluoroolefins is directed towards the use of pairs of adjacent metals to perform the activation 9d. 16 We have shown that fluoroolefins containing a pair of geminal fluorine atoms can coordinate to binuclear systems in a bridging mode, in which they are highly susceptible to CF activation 9d. 16 In addition, when the environments of the two metals differ, olefin activation can be both stereo‐ and regioselective.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…GC-MS of the gas phase above the reaction mixture using an SPME (solid phase microextraction) probe as well as NMR spectroscopic monitoring of the solution (an example of an 1 H{ 2 H} NMR spectrum is depicted in Figure S7 in the Supporting Information) showed that all possible isotopomers of propene and butenes are present. We were also able to detect labeled methane (CH 3 In conclusion, a novel Pd 4 complex has been discovered that contains both CH 3 and m-CH 2 groups in close proximity on the tetranuclear platform, and several intermediates have been spectroscopically identified during its formation from binuclear precursors. This unique Pd 4 system reacts with ethylene to give mainly propene (and some butenes), which has been investigated by isotopic labeling.…”
Section: Angewandte Chemiementioning
confidence: 93%
“…Bi-and oligonuclear complexes currently attract significant attention in the chemical community, mainly because cooperative effects of adjacent metal ions are expected to lead to unique substrate activation modes and to novel reactivity patterns. [1] While much of the work in this field is inspired by natural enzymes that contain multinuclear active sites, [2] recent years have also seen growing interest and impressive progress in the development of non-biomimetic binuclear complexes for two-center organometallic catalysis, [3,4] including the homogeneous polymerization of olefins. [5,6] An interesting situation arises for multinuclear complexes that contain more than two metal ions, as little is known about the synergetic effects in such systems.…”
mentioning
confidence: 99%